«Those fleeing from the cruelty of the owners should be taken under the protection of…»: prisoners and fugitives on the Kuban border in the 20s of the xix century (according to the State archive of Krasnodar region) - N. S. Tkalenko (Гуманитарные и юридические исследования)
The geopolitical realities that developed as a result of the victory of the Russian Empire in the war against Turkey in 1787 – 1791 carried new challenges for St. Petersburg related to the arrangement of the border along the Kuban River. Here it was necessary to build relations with the mountain peoples, whose specific way of life could not be unconditionally accepted by the Russian side. Raids aimed at capturing prisoners have become a serious challenge to good-neighborly relations. This provoked retaliatory military actions, which further complicated the process of peaceful coexistence.Not only military personnel, but also representatives of the civilian population living in settlements located near the border cordon were captured by the highlanders. Many polonyaniks, having passed the most difficult conditions of slave life, sometimes got the opportunity to escape from captivity, and the only salvation for them was the Russian border. The Adygs also ran out here, who often found themselves in captivity with their compatriots as a result of internecine strife. In the hope of receiving protection on the right bank of the Kuban, representatives of the Adyghe dependent estates also left, who experienced increasingly increasing feudal and serfdom oppression from their owners. The tsarist administration provided protection and guaranteed freedom to the Circassian poor, captive Nogais and Tatars who fled to the Russian side. This led to complications in relations with the mountain aristocracy, provoked new military clashes. It was not possible to overcome mutual hostility and build a model of relations that would suit all parties to intercultural dialogue during the period under review.